Addressing differences in learning readiness and style - Showstack, Jonathan (Revista Hipótese, 2017)
There are many different ways to think about Summerhill and A. S. Neill’s philosophy of education. My intent here is not to add to the academic literature about Summerhill or Neill’s ideas, but to offer some brief thoughts and ideas based on my own experiences and observations. This experience includes attending Summerhill for a year when I was a teenager and later (much to my surprise) spending my entire adult life in academia. I focus on one aspect of education that is implicit in, but possibly goes beyond, some of Neill’s ideas: The differences in the ways each of us absorb and process information, particularly in an academic setting.
Keywords: Education; Neill; Summerhill